More-than-humanizing the Anthropocene - Affifi, Ramsey (The Trumpeter)

(untitled) (Athabasca University Press, 2016)
The concept ‘human’ has to be more-than-humanized, a project Abram initiated but left incomplete in his study of language. Doing so is a powerful antidote to some of the more anthropocentric consequences of Anthropocenic thinking. Crucial to this project is uncovering the ways in which human agency is permeated by and circulates within vast causal relationships. Shifting from ecologically destructive patterns suggests completing this phenomenological project by uncovering the sense that the ‘human’ is in no simple sense, ‘steering this vessel.’ Not even the pervasive and perpetual arrogance about our own powers is incontrovertibly ‘our own.’ Humility and awe before these wild and undomesticatable processes cycling through us and carrying us in their currents can correct hubristic assumptions about our power for good or evil, and thereby also perhaps these destructive patterns.